Secretome Analysis of a Pseudomonas aeruginosa Strain Grown Under High Alkane Stress - Hemamalini, R.; Kumar Khare, Sunil (Current Proteomics, 2015)
The effect of alkanes, viz. n-hexane, n-heptane and n-octane on the extracellular proteome and secretome of a solvent tolerant Pseudomonas aeruginosa has been described. Superoxide dismutase, GroEL, A-type flagellin and the porin OprF were altered significantly. The presence of these proteins in the extracellular proteome of solvent-grown cells indicates their role in the cellular adaptation of the strain to a high alkane environment. Up regulation of superoxide dismutase indicates creation of oxidative stress for the bacterial cell in an alkane-rich environment. This secretome analysis is useful for gaining a better understanding of the solvent mediated oxidative stress and the role of superoxide dismutase and GroEL expression as possible markers of solvent tolerance.
Keywords: OprF